2006
DOI: 10.1097/01.wco.0000200544.29915.cc
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning: its relevance to stroke recovery and neurorehabilitation

Abstract: Motor learning mechanisms are operative during spontaneous stroke recovery and interact with rehabilitative training. For optimal results, rehabilitation techniques should be geared towards patients' specific motor deficits and possibly combined, for example, CIMT with VR. Two critical questions that should always be asked of a rehabilitation technique are whether gains persist for a significant period after training and whether they generalize to untrained tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
776
2
60

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,055 publications
(853 citation statements)
references
References 45 publications
(44 reference statements)
15
776
2
60
Order By: Relevance
“…Rehabilitation can be intended as a re-learning process aimed at regaining movements with functional purposes to satisfy personal needs [39]. Using the regenerative capacity of the CNS, rehabilitation therapy can be deployed as a process of movement re-learning targeted to recovery of motor function [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation can be intended as a re-learning process aimed at regaining movements with functional purposes to satisfy personal needs [39]. Using the regenerative capacity of the CNS, rehabilitation therapy can be deployed as a process of movement re-learning targeted to recovery of motor function [11].…”
Section: Resultsmentioning
confidence: 99%
“…This area of study can be divided into three branches, which are at a relatively early stage of development. The first branch of investigation concerns the study of molecular and cellular mechanisms of normal movement as well as the pathophysiological processes leading to paresis after stroke [38,39]. The understanding of pathophysiological mechanisms associated with post-stroke paresis should lead to improvement of impaired functions and more effective recovery than those currently available.…”
Section: Neuroplasticity and Brain Repair After Strokementioning
confidence: 99%
“…According to the feedback we collected and based on previous literature research [4], [5], [17], the tasks identified as fundamental for regaining independence in ADL were: eating, drinking, toileting and using devices for communication (such as smartphones and computers). Many of these tasks can be performed through the combination of a restricted set of hand motions: power grasp (using all fingers, e.g.…”
Section: ) Design Requirementsmentioning
confidence: 99%
“…MANO The mano device was designed with the main purpose of enabling intensive use during ADL by a wide range of users with motor disabilities, while preserving as much as possible patterns of natural interactions with these settings. Several studies have highlighted how ecological interactions with meaningful and relevant environments can lead to increased acceptance of assistive devices and to a better recovery with respect to therapies performed in hospital settings [4], [5]. To this end, we aimed at developing a device intensively usable in ADL, both for assistive and neurorehabilitative purposes.…”
mentioning
confidence: 99%
“…Cortical changes have been shown to occur only with learning of new skills and not just with repetitive use [8,24], suggesting that motor learning mechanisms are operative and critical during brain plastic http://www.jneuroengrehab.com/content/11/1/25 recovery. Understanding the underlying mechanisms of motor learning during robotic locomotor training is crucial to improve the efficacy of robotic training in patients [25]. We seek to tailor the control algorithm to the patientspecific recovery stage to improve robotic training.…”
Section: Introductionmentioning
confidence: 99%